Detection of changes related to breast cancer using charge sensors or mass sensors coupled to DNA monolayers - Batistuti, Marina Ribeiro (2017)
The electrochemical biosensor has been extensively used due to its capacity for rapid and accurate detection of a wide variety of target molecules or biomarkers. DNA hybridization sensors are based on the increase of negative charge on the electrode surface after the DNA target hybridize to the immobilized probes. The development of this platform requires first an understanding of the immobilization process and optimization of surface probe density. In this thesis the electron transfer is investigated on a label-free DNA hybridization detection by its intrinsic charge. The investigation using different immobilization buffers shows a strong dependence on their composition and concentration, and also the influence of the probe and spacer co-immobilized to obtain an organized and compact self-assembled monolayer. The probe density is determined using the chronocoulometry method with hexaammineruthenium (III) chloride, where the value is calculated from the number of cationic redox molecules electrostatically associated with the anionic DNA backbone and presented a linear relationship between thiol molar fraction and probe density from 2 to 5 x 1012 molecules/cm2. The effect of hybridization was determined using electrochemical impedance spectroscopy using negatively charged ferri/ferrocyanide redox couple in solution. After probe surface density optimization, the maximum shift of charge transfer resistence (20%) upon 1 M complementary sequence was obtained with around 25% probe fraction immobilized vii viii on surface. This electrochemical platform developed was able to detected 100 pM of target sequence and distinguish mismatched sequences. The limit of detection is higher when compared to the literature, however, this system can be further improved by amplifing the signal. The same platform is reproduced in the quartz crystal microbalance system and with field-effect transistor, comparing the different detections. The same platform is tested using two different HER2 aptamer sequences. Biological aspects are explored for a better understanding of the system